Democracy's rebirth : the view from Chicago - Simpson, Dick W. (University of Illinois Press, 2022)
"In the third decade of the 21st century we face major challenges to democracy. We are struggling to build a multi-racial, multiethnic democracy based upon political and social equality. We are finding it especially difficult to create an economy that empowers everyone and distributes economic rewards fairly without extreme gaps between rich and poor. The challenges to democracy are both theoretical and very practical. A rather remarkable consensus has emerged among scholars--especially, among political scientists--about the problems we face. There is less consensus about what can be done to confront those problems. In Democracy's Rebirth, Dick Simpson synthesizes the theoretical and empirical studies from many different authors, merges it with his own practical political experience, to frame a single coherent vision of what is to be done at this critical juncture in our history. The result is both a theoretical discourse and a practical manifesto. With 50 years of political research and his unique perspective as a former political candidate, elected official, campaign strategist, and government adviser, Simpson outlines the local, national, and global challenges to democracy. For Simpson, the challenges exist not only at the national level but in cities like Chicago, so he uses Chicago as a case study of how these social, political, and economic challenges play out at the local level. The goal is not utopia, not heaven on earth. However, if democracy is to be reborn in Chicago and America, we must create a more participatory democracy but also a better, more deliberative democracy, led by strong democratic leaders"--